SPATIAL INACTIVITY AND EXISTENTIAL CATASTROPHE: A COMPARITIVE ANALYSIS OF WAITING FOR GODOT AND THE LAST METAPHOR - Tajalla Qureshi; Muhammad Adnan; Safa Zaheer (International Journal of Contemporary Issues in Social Sciences, 2024)
This research study underscores the finding of the concept of absurdity under the theme of existentialism in both plays---Waiting for Godot (1952) by Samuel Beckett and The Last Metaphor (2014) by Usman Ali. Both the plays illustrate the elements of absurdity that is found in the existentialist belief and the choices that we make are impudent. The context of the research study is related to absurdity in the light of World war II. It also caters the existence of human being on the earth. It vehemently shows the futility. Furthermore, the explication highlights the commonality and parallel perception of underlining the humanistic aspects. The researcher showcases that the problem conferred in this paper is related to the term absurdity taken from Albert Camus's The Myth of Sisyphus (1955) and the comparative investigation of the subsequent concept of existentialism in both plays. The researcher[s] draws the framework from both of the books The Myth of Sisyphus and Theater of Absurd by Martin Essline. The characters have been portrayed skillfully utilizing absurd edifice and elegance.